2012
DOI: 10.5513/jcea01/13.4.1130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary palm oil on growth and carcass composition of Heterobranchus longifilis fingerlings

Abstract: This study investigated the effects of dietary palm oil (PO) on growth performance and carcass composition of Heterobranchus longifilis with the goal of replacing dietary fish oil with palm oil. In this study triplicate groups of H. longifilis fingerlings were fed the experimental diets for 8 weeks. Five isonitrogenous (45% crude protein), isoenergetic (20 KJg-1) experimental diets were made containing either 6.0% FO and 0% PO, 4.5% FO and 1.5% PO; 3.0% FO and 3.0% PO; 1.5% FO and 4.5% PO; or 0% FO and 6.0% PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
3
16
1
Order By: Relevance
“…fed different levels of Palm oil were not statistically different after 8 weeks. Inverse relation between body protein and lipid content was observed in this study and is in accordance with reported works by Jokumsen and Aisted, (1990);Bell et al, (2002) in Salmonids and by Babalola and Adebayo, (2007).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…fed different levels of Palm oil were not statistically different after 8 weeks. Inverse relation between body protein and lipid content was observed in this study and is in accordance with reported works by Jokumsen and Aisted, (1990);Bell et al, (2002) in Salmonids and by Babalola and Adebayo, (2007).…”
Section: Resultssupporting
confidence: 81%
“…Caballero et al, (2004) had reported that the reduction of dietary essential fatty acids due to the inclusion of vegetable oils in the diets of fish tends to promote fat accumulation in the liver of sea bream. Babalola and Adebayo, (2007) however, reported that lipid, ash, protein, crude fibre, and moisture composition of Heterobranchussp. fed different levels of Palm oil were not statistically different after 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that substantial use of vegetable oils as energy sources in fish diets yielded positive growth responses in fish (Babalola and Adebayo, 2007). The results obtained in this study have shown that plant-based oil sources could be used as excellent nutrient base in catfish feed manufacture.…”
Section: Resultsmentioning
confidence: 58%
“…Recent studies have revealed that substantial use of vegetable oils as energy sources in fish diets have yielded positive growth response in fish [37,38]. The results gathered from the study have demonstrated that the three lipids source used are of good nutrient composition.…”
Section: Discussionmentioning
confidence: 93%